Peningkatan Kemampuan Menulis Laporan Observasi Melalui Model Pembelajaran Kontekstual pada Mahasiswa D-III Sekretari Universitas Pamulang - Nurhayati Nurhayati; Lisa Novia; Annie Rufeidah (Eduka : Jurnal Pendidikan, Hukum, dan Bisnis, 2022)
The purpose of this research was to determine the increase in the student’ ability of Secretary Diploma at Pamulang University in writing observation reports through a contextual learning model. The subjects of this research were Secretary Diploma’ students of semester VI regular C class 644 with a total of 36 students. The method used in this research is CAR (Classroom Action Research) with a quantitative analysis approach. Data collection techniques in the form of written tests, and documentation studies. The results of the research in the initial test there were no students who succeeded in accordance with the minimum completeness score of 70 with an assessment result of 51.16, then in the final test one only eleven students who had succeeded according to the minimum completeness score with an assessment result of 67.48, then on the final test two, all students had succeeded in accordance with the minimum completeness score with an assessment result of 82.29. The conclusion of this research is through the contextual learning model, Indonesian language learning and students' ability to write reports can be improved.Keywords: contextual learning; writing ability; report; observation